The impacts of non-administered estates in West Malaysia: an analysis - Halim, Akmal Hidayah; Mohd Yusoff, Rahmawati (Serials Publications Pvt. Ltd., 2019)
In Malaysia, non-administered estate refers to the estate of a deceased owner that has not been administered by the beneficiaries even after six months has passed from the owner’s death. The non-administered estates in West Malaysia are governed by the Small Estate (Distribution) Act 1955, the Public Trust Corporation Act 1995, and the Probate and Administration Act 1959. However, the estate administration procedures have lacuna as the system does not assist to trace the estates if no application is made by the beneficiaries to administer such estates. Consequently, the total number of non-administered estates cannot be determined, despite claims that these estates have various impacts. Accordingly, this paper aims to analyse the impacts of non-administered estates from the Islamic, socioeconomic, and legal viewpoints. The discussion adopts the doctrinal analysis through examination of the current primary and secondary materials such as case law, statutory provisions, and other non-legal and legal literature. This paper reveals that the impact of non-administered estates from the legal perspective are reversion, forfeiture, acquisition of land by the Government, multiple death, and non-exercisable owner’s rights. From the Islamic perspective, the impacts are inconsistency with maqasid shariah, misappropriation of property, and problem associated with the deceased’s unpaid debt. Meanwhile, the impacts from socioeconomic perspective are depreciation of estate’s value, loss of income, and deprivation of property.